A Surveillance Model for Skin Cancer in Organ Transplant Recipients: A 22‐Year Prospective Study in an Ethnically Diverse Population. Issue 1 (16th October 2012) - Harwood, C. A.; Mesher, D.; McGregor, J. M.; Mitchell, L.; Leedham‐Green, M.; Raftery, M.; Cerio, R.; Leigh, I. M.; Sasieni, P.; Proby, C. M.
<x xml:space="preserve">Abstract</x> Skin cancer is a frequent complication of organ transplantation. Current guidelines advise specialist skin surveillance but there are limited data on how these should be implemented. This study determines overall burden of cancer and relevant intervals for strategic surveillance in an ethnically diverse transplant population. Prospective data on time to first and subsequent cancers and cumulative burden with respect to defined risk factors were analyzed in a cohort of 1010 patients in a UK center over 22 years. Among 931 individuals transplanted >6 months (mean 10.3 years), 1820 skin cancers occurred in 267 (29%) individuals and were multiple in 66%. Cumulative incidence at 5, 10, 20 and 30 years was 11%, 25%, 54% and 74%, with median time to second, third and fourth cancers of 24, 14.7 and 8.4 months, respectively. Tumors were overwhelmingly squamous and basal cell carcinomas (73% and 24%, respectively). Skin phototype, ultraviolet radiation exposure, age at transplant and duration of transplant were significant risk predictors and were used to construct clinically relevant surveillance intervals. This study provides a comprehensive, prospective analysis of skin cancer morbidity and risk in an ethnically diverse transplant population from which we derive an evidence‐based skin cancer surveillance program.